2007
DOI: 10.1007/bf02983992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of different long-term iron-chelation regimens on myocardial and hepatic iron concentrations assessed with T2* magnetic resonance imaging in patients with β-thalassemia major

Abstract: The aim of this study was to compare the effect of different long-term chelation regimens on heart and liver iron stores with the use of T2* magnetic resonance imaging (MRI) in patients with transfusion-dependent beta-thalassemia major. Sixty-four patients (28 men, 36 women; mean age, 26.49 +/- 5.8 years) were enrolled in the study. The 3 groups were based on the chelation therapy received. The first group (19 patients) received deferiprone (DFP) (75 mg/kg per day orally), the second group (23 patients) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Group A patients had significant higher serum ferritin levels compared with the patients with normal single ROI T2* value (Group B). In fact, as widely reported in the literature, liver T2* is strongly and inversely correlated with serum ferritin concentration (25,26). Moreover, Group A was younger and, consequently, had undergone chelation therapy for a shorter time.…”
Section: Discussionmentioning
confidence: 51%
“…Group A patients had significant higher serum ferritin levels compared with the patients with normal single ROI T2* value (Group B). In fact, as widely reported in the literature, liver T2* is strongly and inversely correlated with serum ferritin concentration (25,26). Moreover, Group A was younger and, consequently, had undergone chelation therapy for a shorter time.…”
Section: Discussionmentioning
confidence: 51%
“…In agreement with our results, Anderson [12] reported that a marked discordance was observed between hepatic and cardiac iron concentration. Also Di Tucci et al [28], Tanner et al [29], Perifanis et al [30], and Wood et al [17] reported that no correlation was found among liver T2*, cardiac T2*, and iron concentration levels.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate chelation therapy usually prevents the development of liver fibrosis in hepatitis C-free BTM patients and reduces the risk of developing severe fibrosis in thalassemics with chronic hepatitis C [14]. Patients who undergo combination therapy with deferiprone and deferoxamine have a significant reduction in hepatic and myocardial iron overload when compared with deferoxamine monotherapy [15]. Liver biopsy could be substituted by noninvasive methods; hepcidin measurements may allow a more accurate assessment of the degree of iron overload and the [16]; and R2 * -MRI measurements are also suggested for predicting hepatic iron content [17].…”
Section: Liver Biopsymentioning
confidence: 98%